From naturalistic neuroscience to modeling radical embodiment with narrative enactive systems - Tikka, Pia; Kaipainen, Mauri Ylermi (Frontiers in Human Neuroscience, 2014)
Mainstream cognitive neuroscience has begun to accept the idea of embodied mind, which assumes that the human mind is fundamentally constituted by the dynamical interactions of the brain, body, and the environment. In today’s paradigm of naturalistic neurosciences, subjects are exposed to rich contexts, such as video sequences or entire films, under relatively controlled conditions, against which researchers can interpret changes in neural responses within a time window. However, from the point of view of radical embodied cognitive neuroscience, the increasing complexity alone will not suffice as the explanatory apparatus for dynamical embodiment and situatedness of the mind. We suggest that narrative enactive systems with dynamically adaptive content as stimuli,may serve better to account for the embodied mind engaged with the surrounding world. Among the ensuing challenges for neuroimaging studies is how to interpret brain data against broad temporal contexts of previous experiences that condition the unfolding experience of nowness. We propose means to tackle this issue, as well as ways to limit the exponentially growing combinatoria of narrative paths to a controllable number.